Application of Moringa leaves (Moringa oleifera), acidifiers, and probiotics as natural growth promoters to improve broiler chicken growth performance: A review - Amalia, Titis Putri Dika; Annisa, Syifa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The use of AGP as a feed additive is 96.97% utilized to stimulate growth and suppress infections by pathogenic microorganisms in the digestive tract. Long-term use of AGP can cause genetic mutations by pathogenic agents, resulting in decreased effectiveness of antibiotic therapy. Moringa is a plant that grows well in tropical areas and is widely known as a vegetable and traditional medicine containing various active compounds such as alkaloids, flavonoids, steroids, triterpenoids, and tannins. Methods: The research method is a literature study by analyzing secondary data based on reviews from several research journals related to the potential of moringa leaves, acidifiers, and probiotics in improving the growth performance of broiler chickens. Findings: These compounds act as antioxidants, antibacterials, and hepatoprotective agents, improving broiler chickens' carcass quality. This composition can be supported by the administration of acidifiers in the form of organic acids to inhibit the growth of pathogenic bacteria in the digestive tract, thereby optimizing the growth process of broiler chickens. Digestive bacterial balance can be achieved by administering probiotics, which play a role in enhancing immunity, health, and growth at all ages and classes of poultry, improving the balance of healthy bacteria in the digestive tract, promoting intestinal integrity and maturation, preventing inflammation, increasing feed intake and digestion by enhancing digestive enzyme activity, reducing bacterial enzyme activity, lowering ammonia production, neutralizing enterotoxins, and stimulating immune function. Conclusion: The combination of these three compositions is expected to provide optimal results for broiler chicken performance. Novelty/Originality of this Article: This article highlights a combined approach using moringa leaf compounds, acidifiers, and probiotics as an alternative to AGP in broiler feed, aiming to achieve optimal growth performance while avoiding the risks associated with antibiotic resistance.